Elevation in surface temperature of root canals obturated with different thermoplasticized gutta-percha obturation techniques-an in vitro study - Al-Shimari, Samer A; Al-Nuaimi, Nassr Ezzulddin (Journal of Baghdad College of Dentistry, 2014)
Background: Many studies have been conducted to evaluate the effect of using a hot material in the root canal and its potential for causing damage to the tooth supporting structure.Materials and methods: thirty permanent premolars were obturated with thermoplasticized Gutta-Percha using three different obturation techniques: soft core, Thermafil, and obtura to evaluate the rise in temperature on the root surface using a multipurpose digital thermometer.Results: temperature increases was significantly greater for Obtura versus Soft core (p